A global ICT skills offensive to bridge the digital divide between north and south - Andreas Stamm (Deutsches Institut für Entwicklungspolitik (DIE), 2001)
Information and communication technologies (ICTs) are increasingly penetrating corporate processes, information processing and the exchange of data between individuals, organizations and firms. This trend emanates from large “old economy” enterprises, and it is affecting more and more sectors of the economy and society.The digital revolution offers developing countries a wide range of opportunities: the use of ICTs and the Internet can improve the supply of information and high-quality educational and medical services to the public, and global networking is creating new economic opportunities and may contribute to democratization and political participation by strengthening organizations in civil society.In many developing countries the use of ICTs is still hampered by a lack of network connections and hardware. As a result of the interplay of new technological options and a targeted commitment by governments, international organizations, enterprises and non-governmental organizations, however, the technological conditions for the use of ICTs are rapidly improving even in the poorer developing countries.A crucial obstacle to the use of ICTs will, on the other hand, be the absence of appropriate skills. The training systems in developing countries are not prepared for training experts in sufficient numbers. At the same time, the global shortage of ICT experts is leading to an increase in international migration to the industrialized countries.As a global labour market in ICT experts emerges, there must be overall, global responsibility for ensuring the renewed and ongoing qualitative development of human resources. As part of an internationally coordinated ICT skills offensive governments, the private sector and non-governmental organizations must help to develop expertise, efficient institutions and international research networks.
Keywords: 330